Analysis of Students' Creative Thinking Ability in Solving SPLDV Problems Assisted by GeoGebra Software Based on Initial Abilities - Wuri, Wuri Indah Murwaningsih; Tatag Eko Yuli Siswono (Universitas Negeri Surabaya, 2022)
This study aims to describe the level of creative thinking ability of students in solving problems on SPLDV material using GeoGebra software based on initial abilities. This research is a descriptive research involving three junior high school students from Sidoarjo. Research instruments in the form of initial ability tests and mathematical creative thinking ability tests using GeoGebra software. Data analysis techniques are carried out through the stages of data reduction, data presentation, and conclusions. The results show, subjects with high creative thinking skills are able to meet 2 indicators of creative thinking, namely fluency and flexibility so that they are categorized into level 3 indicators of creative thinking (creative). Subjects with the ability to think creatively in the medium category are able to meet 1 indicator of creative thinking, namely novelty so that it is categorized into level 2 indicators of creative thinking (quite creative). Subjects with low creative thinking ability are able to meet 1 indicator of creative thinking, namely fluency so that it is categorized into level 1 indicator of creative thinking (less creative). The possible causes of the results in this study were discussed in order to get a number of recommendations for further research.